Modern approaches to the efficiency assessing of created vehicles - A. G. Silyuta; A. G. Silyuta; D. M. Mayakov (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. The manufacturers currently develop new locomotives considering operating conditions with further locomotive fixation on the target ground. They also calculate the operational locomotive models with the key indicators for assessing the cost of the life cycle during the engineering stage. Therefore, the basic information for making operational decisions on purchase about selected locomotive items is the evaluation of the traction rolling stock effectiveness. The manufacturers of other vehicle types have similar aims in terms of operating conditions, engineering features, etc.Materials and methods. The scientists succeed in the usage of the modern evaluating approaches to the vehicles efficiency. The application of the similar criteria that differ in the calculation mechanism and the initial data volume is especially important in evaluating the effectiveness of the multimodal transportation of freight and passenger traffic. The article presented the critical analysis of the main approaches to assessing the effectiveness of the road, water and railway vehicles. Thus, the authors concluded that the manufacturers should consider both the efficiency of the vehicle and the usage intensity.Results. The authors demonstrate quantitative estimates of the proposed efficiency criterion for certificate features and considering real operational conditions. The paper presents the simulation results comparison with the calculation ones considering certificate features. Thus, operational conditions significantly effect the efficiency criterion.Discussion and conclusion. The authors highlight that the obtained results are universal for evaluating the effectiveness of the various vehicles in terms of different rolling stock features.